Berries and anthocyanins: promising functional food ingredients with postprandial glycaemia-lowering effects. Issue 3 (12th May 2016) - Castro-Acosta, Monica L.; Lenihan-Geels, Georgia N.; Corpe, Christopher P.; Hall, Wendy L.
Abstract : The prevalence of type 2 diabetes (T2D) is predicted to reach unprecedented levels in the next few decades. In addition to excess body weight, there may be other overlapping dietary drivers of impaired glucose homeostasis that are associated with an obesogenic diet, such as regular exposure to postprandial spikes in blood glucose arising from diets dominated by highly refined starches and added sugars. Strategies to reduce postprandial hyperglycaemia by optimising the functionality of foods would strengthen efforts to reduce the risk of T2D. Berry bioactives, including anthocyanins, are recognised for their inhibitory effects on carbohydrate digestion and glucose absorption. Regular consumption of berries has been associated with a reduction in the risk of T2D. This review aims to examine the evidence from in vitro, animal and human studies, showing that berries and berry anthocyanins may act in the gut to modulate postprandial glycaemia. Specifically, berry extracts and anthocyanins inhibit the activities of pancreatic α-amylase and α-glucosidase in the gut lumen, and interact with intestinal sugar transporters, sodium-dependent glucose transporter 1 and GLUT2, to reduce the rate of glucose uptake into the circulation. Growing evidence from randomised controlled trials suggests that berry extracts, purées and nectars acutely inhibit postprandial glycaemia and insulinaemia following oral carbohydrate loads. Evidence to date presents a sound basis for exploring the potential for using berries/berry extracts as an additional stratagem to weight loss, adherence to dietary guidelines and increasing physical exercise, for the prevention of T2D.